System of insurance against risks of investment activity in Armenia is an important component of the investment climate - Петросян, С. А.; Манучарян, М. Г. (Scientific Progress & Innovations, 2013)
Importance of insurance of investment risks for attracting foreign investments in Armenia is grounded in this article. The proper information support is important to foreign investors to reduce the degree of political risk. As practice shows, regardless of the real state of investment situation of this country, foreign investors are inclined to examine as a country with the highest degree of risk that country about which they have a minimum information. For the future of Armenia, this fact is extremely important. And as Republic Armenia is a «young» country (since the moment of declaration of independence at the beginning of the 90s), with the limited space, small quantity of population, disposed in an unstable region with complicated political relationships with two neighbouring countries (Azerbaijan and Turkey), Armenia does not always properly appear before a foreign investor as politically, economically and culturally developed country.